Moments, Exponential Sums, and Monodromy Groups - Nicholas M. Katz; Pham Huu Tiep (Forum of Mathematics, Sigma)
We determine the geometric monodromy groups attached to various families, both one-parameter and multi-parameter, of exponential sums over finite fields, or, more precisely, the geometric monodromy groups of the